Artificial Intelegence pada Game Edukasi Angka Romawi Menggunakan Metode Steepest-Ascent hill Climbing - Karnadi, Very (LPPM STIKOM Tunas Bangsa, 2023)
Artificial intelligence is a part of science that really helps human work in everyday life. Artificial intelligence has a broad scope so that artificial intelligence can be implemented in various branches of science, for example the ancient Roman letter recognition game. This game completes the game in the form of sequential ancient roman typesetting according to the Ascent hill Climbing Algorithm concept. The problem with this game is that errors often occur in composing the order of Roman letters, making it difficult to complete this puzzle game. The purpose of this study is to make it easier for puzzle game players to solve the Roman letter number arrangement game according to the rules of the Ascent hill Climbing algorithm. The Ascent hill Climbing algorithm performs the process of finding the highest value to find the final solution. The working system of this algorithm uses the heuristic function. The process of completing this research consists of 9 cities with the working principle of changing the position of the boxes into a sequence of ancient Roman letters correctly according to the final state of the puzzle. There are 4 rules that must be carried out to get the final solution, namely by changing the puzzle position to the right position, to the left position, the upper position and the lower position until the puzzle position is correct according to the sequence and final state. The puzzle consists of a sequence of ancient Roman letters consisting of I,II,III,IV,V,VI,VII,VIII,IX. The completion iteration process occurs 5 times to obtain the final value